Radiotherapy alone in locally advanced cervical cancer: a palliative treatment? Real-world data - Braz, Tiago Pontes; Paulino, Eduardo; Garces, Alvaro Henrique Ingles; Reisner, Rachele Grazziotin; Guitmann, Gustavo; Thuler, Luiz Claudio Santos; Melo, Andreia Cristina de (Brazilian Journal of Oncology, 2021)
Objective: To investigate the benefit of radiotherapy alone in patients diagnosed with locally advanced cervical cancer when the addition of chemotherapy was contraindicated. Methods: A single-center cohort study of patients diagnosed with locally advanced cervical cancer as defined by the FIGO 2009 (stage IB2 to IVA) and contraindication for concomitant chemotherapy was retrospectively evaluated. Patients included were treated with radiotherapy in a curative intent and those patients who completed the external beam radiotherapy were considered for brachytherapy. Patient's demographics, reasons for not receiving concomitant chemotherapy and treatment responses were analyzed. Disease-free survival (DFS) and overall survival (OS) were calculated. Results: With a median follow-up of 13.9 months (range 0.10-81.8), the median DFS was 11.6 months (95% CI: 10.2-13.1), and the median OS was 15.9 months (95% CI: 11.5-20.3). Conclusion: This real-world study provides descriptive information confirming that radiotherapy with curative intent should be offered to patients with locally advanced cervical cancer even when chemotherapy is not an option due to clinical or laboratory contraindications.
Keywords: Uterine cervical neoplasms; Radiotherapy; Brachytherapy; Antineoplastic agents.